2018
DOI: 10.1186/s12872-018-0762-z
|View full text |Cite
|
Sign up to set email alerts
|

Association between brain-derived neurotrophic factor and von Willebrand factor levels in patients with stable coronary artery disease

Abstract: BackgroundBrain-derived neurotrophic factor (BDNF) is a neurotrophin involved in angiogenesis and maintenance of endothelial integrity. Whether circulating BDNF levels are associated with von Willebrand factor (vWF) levels, which are indicators of endothelial dysfunction is not known. This study investigated the association between plasma BNDF and vWF levels and whether these biomarkers could predict cardiovascular events at a 12-month follow-up in patients with stable coronary artery disease (CAD).MethodsWe r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 43 publications
4
35
0
1
Order By: Relevance
“…Based on the present results and those of previous studies, we hypothesized that sustained TrkB activation resulted from SS-induced increases in ca ++ levels. The data from the present study suggested that exercise-induced endogenous BDNF possessed greater bioactivity than exogenous BDNF, and confirmed the amplified effect of BDNF within endothelial cells exposed to increased shear force, indicating that endogenous BDNF expression depended on endothelial function in vivo; studies from Jin et al (40) and Prigent-Tessier et al (22) validated these conclusions. Based on these data and previous studies, we hypothesized that exogenous BDNF administration combined with exercise training may assist in alleviating circulatory disturbances in diabetic or hypertensive patients with poor vascular function.…”
Section: Discussionsupporting
confidence: 81%
“…Based on the present results and those of previous studies, we hypothesized that sustained TrkB activation resulted from SS-induced increases in ca ++ levels. The data from the present study suggested that exercise-induced endogenous BDNF possessed greater bioactivity than exogenous BDNF, and confirmed the amplified effect of BDNF within endothelial cells exposed to increased shear force, indicating that endogenous BDNF expression depended on endothelial function in vivo; studies from Jin et al (40) and Prigent-Tessier et al (22) validated these conclusions. Based on these data and previous studies, we hypothesized that exogenous BDNF administration combined with exercise training may assist in alleviating circulatory disturbances in diabetic or hypertensive patients with poor vascular function.…”
Section: Discussionsupporting
confidence: 81%
“…High levels of VWF have been shown to be associated with major vascular events in large observational studies of non‐MPN patients at high cardiovascular risk, which is consistent with its role as mediator of platelet adhesion to the subendothelial matrix and subsequent platelet activation . Increased levels of VWF may then sustain both macro‐ and microcirculatory disturbances in PV.…”
Section: Discussionsupporting
confidence: 55%
“…28,29 All these findings suggest a prevalent activation and degranulation of ECs in PV that may maintain a high release of VWF into the circulation. 30 High levels of VWF have been shown to be associated with major vascular events in large observational studies of non-MPN patients at high cardiovascular risk, [31][32][33][34][35][36][37] which is consistent with its role as mediator of platelet adhesion to the subendothelial matrix and subsequent platelet activation. 38 Increased levels of VWF may then sustain both macro-and microcirculatory disturbances in PV.…”
Section: Discussionmentioning
confidence: 74%
“…38 Treatment of these co-morbid conditions can possibly increase BDNF levels and improve cognitive deficits. 92…”
Section: Adjunctive Medicationmentioning
confidence: 99%